Implementation Of Audio-Visual Media In Science Learning In Class Iv A (Case Study At Tanjung 2 Public Elementary School, 2024/2025 Academic Year) - Vera Para Dila; M. Taufik; Maulida Arum Fitriana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to describe the implementation of audio-visual media in learning Natural and Social Sciences (IPAS) in class IV A of SD Negeri 2 Tanjung in the 2024/2025 academic year. The main focus of this research includes two things, namely: (1) the steps of using audio visual media in the IPAS learning process, and (2) the use of audio visual media in the learning evaluation process.This research used a qualitative approach with a case study method. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis techniques using the Miles and Huberman Model. The results showed that the steps of using audio-visual media started from careful planning by the teacher, selecting media in accordance with the material, implementing learning with the help of learning videos, and closing in the form of discussion and reflection. Audio visual media is not only used in delivering material, but also in the learning evaluation process. Teachers utilize video-based interactive quizzes, as well as digital worksheets inserted in the show to measure student understanding in a direct and fun way.The use of audio-visual media is proven to increase students' learning motivation, facilitate understanding of IPAS concepts, and make the evaluation process more interesting and participatory.This finding shows that audio-visual media can be an effective learning tool, both in delivering material and in the process of assessing student learning outcomes.